The Arabidopsis DCP2 gene is required for proper mRNA turnover and prevents transgene silencing in Arabidopsis - Thran, Moritz; Link, Katrin; Sonnewald, Uwe (Plant Journal, 2012)
Post-transcriptional gene silencing often limits the over-expression of transgenes in transgenic plants. It involves RNA-DEPENDENT RNA POLYMERASE 6 (RDR6), which recognizes aberrant transcripts, such as inaccurately processed or uncapped mRNA, and triggers silencing of target transcripts. Here, we describe the isolation and characterization of an Arabidopsis mutant displaying increased transgene silencing (its1). Reduced accumulation of transgene mRNA in the its1 mutant background was accompanied by accumulation of transgene-specific siRNAs and was overcome by potyvirus infection. We therefore speculated that ITS1 is a suppressor of post-transcriptional gene silencing. Map-based cloning and subsequent complementation revealed that ITS1 encodes DECAPPING 2 (DCP2), which is crucial for decapping, a prerequisite for mRNA degradation. In agreement with the proposed function of DCP2, we found a reduced accumulation of uncapped mRNA in the its1 mutant. Furthermore, silencing in the its1 mutant was dependent on RDR6 function, suggesting that reduced decapping leads to accumulation of aberrant capped mRNA. Hence, we provide evidence for a class of aberrant mRNA that accumulates upon impaired mRNA decapping and triggers post-transcriptional gene silencing in Arabidopsis. As DCP2 knockouts cause post-embryo lethality, we isolated a hypomorphic dcp2 allele, providing insights into mRNA degradation and its interplay with post-transcriptional gene silencing.
Keywords: ITS1; decapping; Arabidopsis; aberrant mRNA; transgene silencing; small RNAs